Normative Study of Law No. 27 of 2022 on the Protection of Personal Data and its Impact on the Fintech Industry in Indonesia - Zuwanda, Zulkham Sadat; Judijanto, Loso; Khuan, Hendri; Triyantoro, Andri (West Science Law and Human Rights, 2024)
The enactment of Law No. 27 of 2022 on Personal Data Protection marks a pivotal moment in Indonesia’s regulatory framework, particularly for industries that handle significant amounts of personal data, such as the financial technology (fintech) sector. This study provides a normative juridical analysis of the PDP Law and examines its impact on the fintech industry. The research focuses on the law’s key provisions, including consent requirements, data breach notification, and data security obligations. Additionally, the study explores the operational challenges fintech companies face in complying with the law, such as the costs of compliance, technical requirements, and the need for employee training. While the PDP Law enhances consumer trust by offering greater protection and transparency, it also presents hurdles that fintech firms must overcome to ensure compliance. The analysis concludes with recommendations for fintech companies to balance legal obligations with innovation to maintain competitiveness in Indonesia’s evolving digital economy.